Bridging Young Learners’ English Proficiency through Interactive Educational Games at SDN Ciheuleut 2, Bogor City - Bonanza, Occy; Abikusno, Rhino; Resmayasari, Ira; Fami, Amata; Barus, Irma Rasita Gloria; Wahyoedi, Bontisesari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This report investigates the integration of interactive educational games aimed at enhancing English language learning in elementary level. Conducted at SDN Ciheuleut 2 in Bogor City, the study focused on three games—